International multi-site survey on the use of online support groups in bipolar disorder. (18th August 2017) - Bauer, Rita; Conell, Jörn; Glenn, Tasha; Alda, Martin; Ardau, Raffaella; Baune, Bernhard T.; Berk, Michael; Bersudsky, Yuly; Bilderbeck, Amy; Bocchetta, Alberto; Bossini, Letizia; Castro, Angela M. Paredes; et al.
Abstract: Background: Peer support is an established component of recovery from bipolar disorder, and online support groups may offer opportunities to expand the use of peer support at the patient's convenience. Prior research in bipolar disorder has reported value from online support groups. Aims: To understand the use of online support groups by patients with bipolar disorder as part of a larger project about information seeking. Methods: The results are based on a one-time, paper-based anonymous survey about information seeking by patients with bipolar disorder, which was translated into 12 languages. The survey was completed between March 2014 and January 2016 and included questions on the use of online support groups. All patients were diagnosed by a psychiatrist. Analysis included descriptive statistics and general estimating equations to account for correlated data. Results and conclusions: The survey was completed by 1222 patients in 17 countries. The patients used the Internet at a percentage similar to the general public. Of the Internet users who looked online for information about bipolar disorder, only 21.0% read or participated in support groups, chats, or forums for bipolar disorder (12.8% of the total sample). Given the benefits reported in prior research, clarification of the role of online support groups in bipolar disorder is needed. With only a minority of patients using online support groups, there are analytical challenges for future studies.